Decarbonising new city precincts: A case study in Perth, Western Australia - Beattie, Colin (Elsevier, 2014)
The performance of our cities in terms of how they deal with energy across a wide range of indicators is the key factor in reducing carbon emissions. The focus of this paper is a precinct in Perth which is about to be redeveloped. The proposed plan is modelled looking specifically at Greenhouse Gas (GHG) emissions from: materials used in the construction, not only of the buildings but also the infrastructure (i.e. roads and paving in the public realm); electricity and gas consumption through the use of everyday residential and commercial appliances and equipment; the energy required for the pumping and treatment of water supplied to the development site including water required for the irrigation of public areas as well as for individual consumption; and private motor vehicles owned by residents on the development site. A baseline model representing the proposed plan built to existing codes and standards is used to determine the impact of a range of low-carbon interventions proposed for the development, including reducing parking and adding good quality public transport. Significant GHG emissions reductions of greater than 50% are possible at quite minimal additional cost due to the alternative systems of development that are found to be effective at a precinct scale. In order to achieve such precinct-scale innovations there are policy and regulatory barriers for electricity, thermal energy and water utility providers to overcome. There needs to be a reasonable business case for developers, energy service companies (ESCO's) and potential customers to enable investment in low carbon, precinct scale options. Some examples of these are also discussed.